A method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys using MAX phase
By using a layered Max phase TI3SIC2 as a secondary phase in the use of the MAX phase of MAX phase in difficult melting metal alloy, the characteristics of the low temperature processing performance and high temperature resistance of high temperature at medium low temperature and high temperature at low temperature and high temperatures are used. The problem of incredible variation performance has achieved dual performance improvement.
Patent Information
- Application Number
- CN202211608217.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The processing performance of refractory metal-based alloys is difficult to compatible with the high-temperature creep resistance at medium and low temperatures. Traditional solid solution strengthening and dispersion strengthening methods cannot simultaneously improve the room temperature ductility and high-temperature creep performance of the alloy.
The layered MAX phase Ti3SiC2 is used as the dispersion-strengthened second phase, and its characteristics of sliding along the basal surface at medium and low temperatures are used to toughen and improve processing performance; it decomposes at high temperatures to form a large number of carbide and oxide hard particles, hindering the position It can prevent cross-slip and grain boundary climbing and enhance high-temperature creep resistance.
The dual improvement of the low temperature and extension of the difficult melting metal consecration alloy and the high temperature resistance resistance have been achieved, and it has obtained good room temperature strong toughness and resistance to high temperature creep.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a metal alloy, and in particular to a method for regulating the low temperature ductility and high temperature creep resistance of a refractory metal-based alloy using a MAX phase. Background Art
[0002] Molybdenum is a rare refractory metal material. Due to its high melting point, high modulus, high wear resistance, good electrical and thermal conductivity, low thermal expansion coefficient, and good acid and alkali resistance and liquid metal corrosion resistance, molybdenum and its alloys have broad application prospects in nuclear energy, aerospace, power electronics, machinery manufacturing, steel metallurgy, medical equipment, military industry and other fields. However, the room temperature brittleness and insufficient room temperature / high temperature strength of molybdenum seriously limit its industrial application. Therefore, only by using alloying methods to obtain molybdenum alloys with good strength and toughness can the application field of molybdenum-based materials be expanded and my country's molybdenum resource advantages be fully utilized.
[0003] As high-temperature structural materials, refractory metals need to face the increasing service temperature requirements for their high-temperature performance. Alloying by adding elements is an important means to regulate and improve the performance of refractory metal materials. Generally, the methods for alloying refractory metals are mainly solid solution strengthening, such as molybdenum-rhenium, tungsten-rhenium alloys, molybdenum-titanium, molybdenum-niobium, molybdenum-silicon alloys, etc., dispersion strengthening such as ODS-Mo, ODS-W alloys, etc., and both strengthening methods are like TZM alloys. Although there are also whisker-strengthened tungsten / molybdenum alloys, due to the difficulty in whisker preparation and the deterioration of performance in the high-temperature environment during the alloy preparation process, there are few whisker-strengthened tungsten / molybdenum alloys for engineering applications. Fine grain strengthening of tungsten / molybdenum alloys is another important method, that is, grain refinement through large deformation. Since the Xi'an Jiaotong University team proposed liquid-liquid doped molybdenum alloys, ODS has become one of the main methods for strengthening refractory metals. Combined with the integrated preparation process of "materials and processing" of refractory metals, high-performance tungsten / molybdenum alloys are basically made by alloying + fine graining + deformation strengthening. As a high-temperature structural material, the high-temperature creep resistance of refractory metals is one of its core performance indicators, especially for long-term high-temperature service environments. High-temperature creep performance is closely related to the composition and structure of the material. Generally speaking, for ODS-Mo alloys, increasing the content of second-phase particles helps to improve high-temperature creep performance, but with the increase of the content of second-phase particles, the uniformity of the alloying elements becomes worse and the processing becomes more difficult. The tungsten-rhenium and molybdenum-rhenium alloys, which are mainly solid solution strengthened, have poor high-temperature creep resistance. Although the creep performance of molybdenum-rhenium alloys improves with the increase of rhenium content, metal rhenium is expensive and has a high density, which seriously limits the application range of molybdenum-rhenium alloys. In addition, when the rhenium content is too high, the alloy is prone to transmutation. It can be seen that traditional solid solution strengthened and dispersion strengthened molybdenum alloys generally have the problem that medium and low temperature processing performance and high temperature creep resistance are incompatible. This is a huge challenge faced by refractory metal-based alloys as high-temperature structural materials.
[0004] Tungsten and molybdenum metals are intrinsically brittle, and the addition of alloying elements can significantly improve the processing and service performance of the materials. A series of tungsten-molybdenum-based alloy materials have been formed. In recent years, with the continuous development of rare earth oxide (ODS) doping technology, ODS dispersion strengthening has become the main means of strengthening and toughening tungsten-molybdenum alloys. At the same time, given that ODS alloys have better creep properties than solid solution-strengthened molybdenum alloys, ODS-strengthened molybdenum-rhenium alloys have come into being. In order to meet the higher performance requirements of molybdenum alloys in the service environment, the addition amount of ODS-strengthened tungsten-molybdenum alloys has been continuously increased. With the increase of dispersion-strengthened phase components, the agglomeration tendency of the second phase elements increases, and the processing performance of the alloy deteriorates. This is especially serious for the preparation of heterogeneous thin-walled tungsten-molybdenum alloy pipes. However, this year, with the need for the application of nuclear-grade molybdenum alloys, thin-walled molybdenum alloy cladding and heat pipes have become new potential application areas. If only the traditional strengthening and toughening ideas are followed, it is obviously impossible to overcome the contradiction between service performance and machinability. It is necessary to find a molybdenum alloy with good machinability at medium and low temperatures and good creep performance at high temperatures. This requires a dispersion strengthening phase that plays a toughening role at low and medium temperatures and a strengthening role at high temperatures. In other words, the new doping element must have the function of thermal deformation. However, the traditional dispersion strengthening phases such as oxides and carbides do not have such properties. Therefore, it is impossible to achieve compatibility between low and medium temperature processing performance and high temperature creep performance.
[0005] From the above analysis, it can be seen that in order to maintain the compatibility of medium and low temperature processing performance and high temperature creep resistance, it is necessary to regulate the composition changes of the alloy in different temperature ranges, rather than simply regulating the organizational structure to balance the comprehensive performance of the alloy, which is the traditional performance optimization method. Summary of the invention
[0006] The object of the present invention is to provide a method for regulating the low-temperature ductility and high-temperature creep resistance of a refractory metal-based alloy by using a MAX phase, which can dually improve the low-temperature processing performance and high-temperature creep resistance. The obtained alloy has fine grains, uniform and dense structure, good room temperature toughness and high-temperature creep resistance.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] Step 1, putting molybdenum powder into a ball mill and ball milling under an argon atmosphere to obtain refined molybdenum powder;
[0009] Step 2, according to the mass percentage, 1% to 3% of MAX phase Ti3SiC2 powder and 97% to 99% of the ball-milled molybdenum powder are placed in a ball mill and ball-milled in an argon atmosphere to obtain a uniformly mixed powder;
[0010] Step 3: Place the mixed powder into a graphite mold, and then place the graphite mold containing the mixed powder into a vacuum chamber with a degree of vacuum of 5×10 -3Pa~1×10 -2 The alloy is sintered at 1400-1500°C in a spark plasma sintering furnace and then pressurized to 30-50MPa and cooled in the furnace. After demolding, the surface layer of the sintered body is removed to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0011] The step 1 is to put molybdenum powder into a planetary ball mill whose ball milling jar and grinding balls are all made of tungsten carbide, with a ball-to-material ratio of 8 to 12:1, and ball milling for 10 to 20 hours at a rotation speed of 200 to 300 r / min to obtain molybdenum powder with a grain size of 1 μm-10 μm.
[0012] The impurities of the MAX phase Ti3SiC2 powder in step 2 are no more than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm.
[0013] The ball milling in step 2 is carried out in a planetary ball mill whose ball milling jar and grinding balls are both made of agate, with a ball-to-material ratio of 1 to 2:1 and a rotation speed of 300-500 r / min for 6 to 12 hours.
[0014] The inner diameter of the graphite mold in step 3 is 30 to 60 mm.
[0015] The sintering time of step 3 is 3 to 10 minutes.
[0016] In step 3, the thickness of the surface layer removed from the sintered body is 0.3-0.5 mm.
[0017] The present invention aims at the problem that molybdenum alloys generally have medium and low temperature processing performance and high temperature creep resistance performance that cannot be achieved at the same time. The layered MAX phase is used as the second phase of dispersion strengthening, and its characteristics of sliding along the base surface at medium and low temperatures are used to achieve toughening of the refractory metal-based alloy, thereby improving the medium and low temperature processing performance of the alloy. At the same time, after the MAX phase is decomposed at high temperature, a large number of carbides and oxide hard particles are formed, which hinder dislocation sliding and grain boundary climbing, and enhance the creep resistance of the refractory metal-based alloy at high temperature. Thus, the dual improvement of medium and low temperature processing performance and high temperature creep resistance is achieved.
[0018] M n+1 AX nPhase, where M represents transition metal elements, A represents main group elements, and X represents C or N elements. It is a layered ceramic with a rock salt-like structure. According to the different values of n in the general formula, it can be divided into M2AX (211 phase), M3AX2 (312 phase) and M4AX3 (413 phase). The crystal structure of the MAX phase belongs to the hexagonal system, with a space group of P63 / mmc, in which the MX layers and the A-group atomic layers are alternately stacked in the c-axis direction, and the X atoms are located in the octahedral gaps of the M atomic layers. The unique crystal structure of the MAX phase gives it unique chemical bond characteristics: M and X are bonded by strong covalent bonds and ionic bonds; M and A are bonded by weaker covalent bonds or metallic bonds, which makes the MAX phase easy to slip along the basal plane
[0001] . The unique bonding configuration and crystal structure make it combine many advantages of ceramics and metal materials, such as high melting point, high elastic modulus, high hardness, good electrical and thermal conductivity, processability, damage tolerance and thermal shock resistance.
[0019] Among them, Ti3SiC2 is a typical MAX phase. Different from the traditional carbide and oxide second phase particles, layered Ti3SiC2 as the second phase in molybdenum alloy can relieve the stress concentration at the interface between Ti3SiC2 and molybdenum matrix through its own microscale plastic deformation at room temperature, delay interface cracking, thereby improving the room temperature ductility of the alloy and ensuring that the alloy has good machinability at medium and low temperatures. In addition, when serving above 1200℃, on the one hand, Si atoms in Ti3SiC2 begin to diffuse into the molybdenum matrix to form a high-strength solid solution, and on the other hand, a large number of dispersed carbides produced by the reaction significantly increase the number of hard second phase particles, significantly enhance the hindrance to dislocation movement, and significantly improve the dispersion strengthening effect. Therefore, molybdenum alloys with the addition of Ti3SiC2 can simultaneously obtain high room temperature ductility, strength and good high temperature creep resistance. DETAILED DESCRIPTION
[0020] Embodiment 1:
[0021] Step 1, in an argon atmosphere, put molybdenum powder into a planetary ball mill whose ball milling jar and grinding balls are all made of tungsten carbide, according to a ball-to-material ratio of 10:1, and ball mill at a speed of 200 r / min for 20 hours to obtain molybdenum powder with a grain size of 1 μm-10 μm;
[0022] Step 2, 1% of MAX phase Ti3SiC2 powder and 99% of ball-milled molybdenum powder are loaded into a planetary ball mill whose ball milling jar and grinding balls are both made of agate, and ball milled at a speed of 400 r / min for 9 hours at a ball-to-material ratio of 1:1 under an argon atmosphere to obtain a uniformly mixed powder;
[0023] Wherein, the impurities of the MAX phase Ti3SiC2 powder are not greater than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm;
[0024] Step 3: Place the mixed powder into a graphite mold with an inner diameter of 30 to 60 mm, and then place the graphite mold containing the mixed powder into a vacuum chamber with a degree of vacuum of 5 × 10 -3 The sintered body was sintered at 1450°C for 8 min in a spark plasma sintering furnace of 1500 Pa and then pressurized to 30-50 MPa and cooled in the furnace. After demolding, the surface layer of the sintered body was removed by 0.3 mm to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0025] Embodiment 2:
[0026] Step 1, in an argon atmosphere, put molybdenum powder into a planetary ball mill whose ball milling jar and grinding balls are all made of tungsten carbide, according to a ball-to-material ratio of 12:1, and ball mill at a speed of 300 r / min for 10 hours to obtain molybdenum powder with a grain size of 1 μm-10 μm;
[0027] Step 2, 2% of MAX phase Ti3SiC2 powder and 99% of ball-milled molybdenum powder are loaded into a planetary ball mill whose ball milling jar and grinding balls are both made of agate, and ball milled for 13 hours at a speed of 300 r / min under an argon atmosphere at a ball-to-material ratio of 1.5:1 to obtain a uniformly mixed powder;
[0028] Wherein, the impurities of the MAX phase Ti3SiC2 powder are not greater than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm;
[0029] Step 3: Place the mixed powder into a graphite mold with an inner diameter of 30 to 60 mm, and then place the graphite mold containing the mixed powder into a vacuum chamber with a vacuum degree of 8×10 -3 Pa spark plasma sintering furnace, sintered at 1400 ° C for 10 minutes, pressurized to 30-50 MPa and cooled in the furnace. After demolding, the surface layer of 0.4 mm of the sintered body was removed to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0030] Embodiment 3:
[0031] Step 1, in an argon atmosphere, put molybdenum powder into a planetary ball mill with a ball milling jar and grinding balls made of tungsten carbide, according to a ball-to-material ratio of 9:1, and ball mill at a speed of 230 r / min for 18 hours to obtain molybdenum powder with a grain size of 1 μm-10 μm;
[0032] Step 2, 3% of MAX phase Ti3SiC2 powder and 97% of ball-milled molybdenum powder are loaded into a planetary ball mill whose ball milling jar and grinding balls are all made of agate, and ball milled at a speed of 450 r / min for 8 hours at a ball-to-material ratio of 2:1 under an argon atmosphere to obtain a uniformly mixed powder;
[0033] Wherein, the impurities of the MAX phase Ti3SiC2 powder are not greater than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm;
[0034] Step 3: Place the mixed powder into a graphite mold with an inner diameter of 30 to 60 mm, and then place the graphite mold containing the mixed powder into a vacuum chamber with a vacuum degree of 9×10 -3 The sintered body was sintered at 1480°C for 5 min in a spark plasma sintering furnace with a pressure of 30-50 MPa and cooled in the furnace. After demolding, the surface layer of the sintered body was removed by 0.5 mm to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0035] Embodiment 4:
[0036] Step 1, in an argon atmosphere, put molybdenum powder into a planetary ball mill whose ball milling jar and grinding balls are all made of tungsten carbide, according to a ball-to-material ratio of 11:1, and ball mill at a speed of 280 r / min for 12 hours to obtain molybdenum powder with a grain size of 1 μm-10 μm;
[0037] Step 2, 1.5% of MAX phase Ti3SiC2 powder and 98.5% of ball-milled molybdenum powder are loaded into a planetary ball mill whose ball milling jar and grinding balls are all made of agate, and ball milled for 10 hours at a speed of 350 r / min under an argon atmosphere at a ball-to-material ratio of 1.3:1 to obtain a uniformly mixed powder;
[0038] Wherein, the impurities of the MAX phase Ti3SiC2 powder are not greater than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm;
[0039] Step 3: Place the mixed powder into a graphite mold with an inner diameter of 30 to 60 mm, and then place the graphite mold containing the mixed powder into a vacuum chamber with a degree of vacuum of 6 × 10 -3 Pa spark plasma sintering furnace, sintered at 1500 ° C for 3 minutes, pressurized to 30-50 MPa and cooled in the furnace. After demolding, the surface layer of 0.5 mm of the sintered body was removed to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0040] Embodiment 5:
[0041] Step 1, in an argon atmosphere, put molybdenum powder into a planetary ball mill with a ball milling jar and grinding balls made of tungsten carbide, according to a ball-to-material ratio of 8:1, and ball mill at a speed of 260 r / min for 15 hours to obtain molybdenum powder with a grain size of 1 μm-10 μm;
[0042] Step 2, 2.5% of MAX phase Ti3SiC2 powder and 97.5% of ball-milled molybdenum powder are loaded into a planetary ball mill whose ball milling jar and grinding balls are both made of agate, and ball milled for 6 hours at a speed of 500 r / min at a ball-to-material ratio of 1.8:1 under an argon atmosphere to obtain a uniformly mixed powder;
[0043] Wherein, the impurities of the MAX phase Ti3SiC2 powder are not greater than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm;
[0044] Step 3: Place the mixed powder into a graphite mold with an inner diameter of 30 to 60 mm, and then place the graphite mold containing the mixed powder into a vacuum chamber with a vacuum degree of 1×10 -2 The sintered body was sintered at 1430°C for 9 min in a spark plasma sintering furnace with a pressure of 30-50 MPa and cooled in the furnace. After demolding, the surface layer of the sintered body was removed by 0.4 mm to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
[0045] The present invention provides a means of medium- and low-temperature micro-plastic toughening and high-temperature pyrolysis-induced strengthening of the MAX phase, which promotes the improvement of the toughness and plasticity of tungsten and molybdenum alloys under medium- and low-temperature conditions; and under certain high-temperature conditions, the pinning effect of hard particles on the grain boundaries is generated by the change of alloy composition, thereby enhancing the high-temperature creep resistance of the alloy.
[0046] The layered MAX phase is used as the dispersion strengthened second phase, and its characteristic of sliding along the basal plane at medium and low temperatures is utilized to achieve toughening of the refractory metal-based alloy, thereby improving the medium and low temperature processing performance of the alloy; the MAX phase is used to form a large number of hard particles such as carbides and oxides after decomposition at high temperature as the dispersed second phase, which hinders dislocation slip and grain boundary climb, and enhances the creep resistance of the refractory metal-based alloy at high temperature; the above two characteristics of the MAX phase are used to obtain a refractory metal-based alloy with both medium and low temperature ductility and high temperature creep resistance.
[0047] By utilizing the characteristics of MAX phase sliding along the basal plane at medium and low temperatures and decomposing at high temperatures to form hard particles, the dual improvements in the medium and low temperature ductility and high temperature creep resistance of refractory metal-based alloys are achieved. In order to avoid the decomposition of MAX phase (Ti3SiC2) during the alloy sintering process and obtain a high-density refractory alloy, the present invention proposes first using high-energy ball milling to activate the matrix powder, and then combining spark plasma sintering (SPS) technology to achieve rapid densification of the alloy at a relatively low temperature. The preparation process is simple and highly controllable.
Claims
1. A method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys by using MAX phase, characterized in that: Step 1, putting molybdenum powder into a ball mill and ball milling under an argon atmosphere to obtain refined molybdenum powder; Step 2, according to the mass percentage, 1% to 3% of MAX phase Ti3SiC2 powder and 97% to 99% of the ball-milled molybdenum powder are placed in a ball mill and ball-milled in an argon atmosphere to obtain a uniformly mixed powder; Step 3: Place the mixed powder into a graphite mold, and then place the graphite mold containing the mixed powder into a vacuum chamber with a degree of vacuum of 5×10 -3 Pa~1×10 -2 The alloy is sintered at 1400-1500°C in a spark plasma sintering furnace and then pressurized to 30-50MPa and cooled in the furnace. After demolding, the surface layer of the sintered body is removed to obtain a molybdenum alloy with added MAX phase Ti3SiC2.
2. The method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: The step 1 is to put molybdenum powder into a planetary ball mill whose ball milling jar and grinding balls are all made of tungsten carbide, with a ball-to-material ratio of 8 to 12:1, and ball milling for 10 to 20 hours at a rotation speed of 200 to 300 r / min to obtain molybdenum powder with a grain size of 1 μm-10 μm.
3. The method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: The impurities of the MAX phase Ti3SiC2 powder in step 2 are no more than 0.1%, and the particle size of the MAX phase Ti3SiC2 powder is 200nm to 800nm.
4. The method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: The ball milling in step 2 is carried out in a planetary ball mill whose ball milling jar and grinding balls are both made of agate, with a ball-to-material ratio of 1 to 2:1 and a rotation speed of 300-500 r / min for 6 to 12 hours.
5. The method for regulating low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: The inner diameter of the graphite mold in step 3 is 30 to 60 mm.
6. The method of controlling the low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: The sintering time of step 3 is 3 to 10 minutes.
7. The method of controlling the low temperature ductility and high temperature creep resistance of refractory metal-based alloys by MAX phase according to claim 1, characterized in that: In step 3, the thickness of the surface layer removed from the sintered body is 0.3-0.5 mm.
Citation Information
Patent Citations
Molybdenum alloy added with MAX phase and preparation method of molybdenum alloy
CN113862540A